Система направлений и фазовых соотношений электромагнитных величин при численных расчетах магнитных полей в турбогенераторе - Милых, В.И.; Полякова, Н.В. (Електротехніка і електромеханіка, 2011)
A system of directions of currents in the windings of a turbogenerator is presented for numerical calculations of magnetic fields. It allows obtaining coordinated phase –time and spatial relationships for a set of electromagnetic parameters which characterize the turbogenerator operation.